2008
DOI: 10.1038/onc.2008.447
|View full text |Cite
|
Sign up to set email alerts
|

XB130, a tissue-specific adaptor protein that couples the RET/PTC oncogenic kinase to PI 3-kinase pathway

Abstract: XB130 is a recently cloned 130 kDa-adaptor protein and Src kinase substrate, structurally similar to actin-filamentassociated protein. Here we show that XB130 is predominantly expressed in the thyroid. Given that XB130 is a thyroid-specific tyrosine kinase substrate, we asked whether it is targeted by RET/PTC, a genetically rearranged, constitutively active, thyroid-specific tyrosine kinase that plays a pathogenic role in papillary thyroid cancer. RET/PTC induced robust tyrosine phosphorylation of XB130, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
108
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(115 citation statements)
references
References 36 publications
5
108
1
1
Order By: Relevance
“…XB130 protein was identified to be expressed in the cytoplasm of thyroid follicular cells in normal thyroid tissue ( Figure 6A), as shown previously. 10 The respective staining also confirmed the presence of XB130 in papillary as well as insular forms of thyroid carcinoma ( Figure 6A). Semiquantitative analysis of cytoplasmic intensity scores demonstrated that the XB130 intensity in papillary thyroid carcinoma and anaplastic/insular carcinoma was significantly lower than that in normal and benign lesion (P Ͻ 0.001), and the intensity in the Hürthle cell carcinoma group was significantly lower than that in the normal group (P Ͻ 0.01) ( Figure 6B).…”
Section: Xb130 Expression In Human Thyroid Carcinomassupporting
confidence: 60%
See 4 more Smart Citations
“…XB130 protein was identified to be expressed in the cytoplasm of thyroid follicular cells in normal thyroid tissue ( Figure 6A), as shown previously. 10 The respective staining also confirmed the presence of XB130 in papillary as well as insular forms of thyroid carcinoma ( Figure 6A). Semiquantitative analysis of cytoplasmic intensity scores demonstrated that the XB130 intensity in papillary thyroid carcinoma and anaplastic/insular carcinoma was significantly lower than that in normal and benign lesion (P Ͻ 0.001), and the intensity in the Hürthle cell carcinoma group was significantly lower than that in the normal group (P Ͻ 0.01) ( Figure 6B).…”
Section: Xb130 Expression In Human Thyroid Carcinomassupporting
confidence: 60%
“…11,12 XB130 couples RET/PTC signaling to the phosphatidylinositol 3-kinase (PI3K)/Akt signaling through a specific binding site to the p85␣ subunit of PI3K, thereby regulating cell survival and proliferation. 10 We further found that XB130 has a strong affinity with the lamellipodial F-actin meshwork and is involved in the motility and invasiveness of tumor cells. 13 The objectives of the present study were to investigate whether XB130 is involved in tumor growth in vivo and to identify the pathogenetic molecular mechanisms.…”
mentioning
confidence: 67%
See 3 more Smart Citations